FEATURE OF ENGINEERING TRAINING FOR FUTURE TECHNOLOGY TEACHERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
A study of the ideas of future technology teachers about technical phenomena in machines showed that their interpretations are unsuitable for organizing the educational process of studying the basics of technology by students. Accordingly, they will not be able to orient lyceum graduates to engineering education. The purpose of this study was to form the interest of future technology teachers in the adapted content of engineering training, suitable for organizing specialized training of lyceum students in studying the basics of technology. The levels of cognitive interests of students were assessed according to qualitative criteria: cognitive activity, nature of interest, independence, nature of use of free time, method of overcoming cognitive difficulties. Quantitative data were collected using questionnaire and testing methods. The null hypothesis of the absence of significant differences in the level of change in students' cognitive interest in technical phenomena was not confirmed in the experimental group, but was confirmed in the control group. The results of this study are important for developing university work programs. The practical value of the research results for the training of students of non-technical specialties lies in defining the concept of a technology user for ideological knowledge about machines. The potential international value of the research results lies in defining technical phenomena in machine drive as a basic concept for the formation of a technical worldview.